Extraction and Analytical Methods for the Characterization of Polyphenols in Marine Microalgae: A Review - Gabriela Bermudez; Cristina Terenzi; Francesca Medri; Vincenza Andrisano; Serena Montanari (Marine Drugs)
Marine microalgae are emerging as promising sources of polyphenols, renowned for their health-promoting benefits. Recovering polyphenols from microalgae requires suitable treatment and extraction techniques to ensure their release from the biomass and analytical methodologies to assess their efficiency. This review provides a comprehensive comparison of traditional and cutting-edge extraction and analytical procedures applied for polyphenolic characterization in marine microalgae over the past 26 years, with a unique perspective on optimizing their recovery and identification. It addresses (I) cell disruption techniques, including bead milling, high-speed homogenization, pulsed electric field, ultrasonication, microwave, freeze-thawing, and enzymatic/chemical hydrolysis; (II) extraction techniques, such as solid–liquid extraction, ultrasound and microwave-assisted extraction, pressurized-liquid extraction, and supercritical CO2; (III) analytical methods, including total phenolic and flavonoid content assays and advanced chromatographic techniques like GC-MS, HPLC-DAD, and HPLC-MS. Key findings showed bead milling and chemical hydrolysis as effective cell disruption techniques, pressurized-liquid extraction and microwave-assisted extraction as promising efficient extraction methods, and HPLC-MS as the finest alternative for precise phenolic characterization. Unlike previous reviews, this study uniquely integrates both extractive and analytical approaches in one work, focusing exclusively on marine microalgae, a relatively underexplored area compared to freshwater species, offering actionable insights to guide future research and industrial applications.